Leading with soul an uncommon journey of spirit - Bolman, Lee G.; Deal, Terrence E. (San Francisco Jossey-Bass, 2001)
Since its original publication in 1995, this book has inspired thousands of readers. Far ahead of its time, it bravely reveals the path to leadership to be a personal journey requiring a knowledge of self and a servant-leader mentality. In this new and revised edition, the authors address such current issues as the changing nature of work, the new face of today's workforce, and the greater need for an infusion of soul in the workplace.
Prelude: In Search of Soul and Spirit -- The Search. 1. The Heart of Leadership Lives in the Hearts of Leaders. 2. The Human Heart Is More Than a Pump. 3. The Journey of a Soul. 4. Discovering New Teachers -- Interlude: Reclaiming Your Soul -- Conviction. 5. A Place to Start. 6. Vicissitudes of the Journey -- Interlude: Leaning into Your Fear -- Gifts. 7. Gifts of Leadership. 8. Authorship. 9. Love. 10. Power. 11. Significance -- Interlude: Community and the Cycle of Giving -- Sharing. 12. Summoning the Magic of Stories. 13. Lifting Our Voices in Song. 14. Celebrating Shared Icons -- Interlude: Expressing the Spirit -- A New Life. 15. The Twilight of Leadership. 16. Deep Refuge -- Interlude: The Cycle of the Spirit. 17. The Legacy -- Postlude: Continuing a Spirited Dialogue -- Soul at Work.
Includes bibliographical references (pages 245-248).
Donated by Atty. Mehol K. Sadain, UP Institute of Islamic Studies, 2018.
Keywords: Leadership -- Moral and ethical aspects; Leadership -- Religious aspects